Climate as a group level phenomenon: Theoretical assumptions and methodological considerations. (27th November 2019) - Luria, Gil
Summary: Climate is a group‐level phenomenon that should be measured and studied at the group level. The group level has theoretical and methodological advantages over the individual level. In this paper, I theoretically review the assumptions in measuring climate at the individual and group levels and demonstrate that the group‐level assumptions are more adequate for climate research because of their influences in exposure to events, interpretation of events, and preservation of perceptions. Methodologically, I discuss advantages in group‐level climate measurement accuracy that are based on multiple evaluators of climate and I suggest group aggregation is an organizational form of "wisdom of the crowds." Finally, I point to three topics that remain to be investigated to understand climate at the group level better. The first is use of variability measures to compensate for information that is lost in aggregation. The second is challenging the assumption that formal organizational structure defines the group boundaries. I suggest that other levels of analysis apply to group‐level climate measurement and demonstrate the use of informal, more natural groups as an additional level. Third, I point to recently developed statistical procedures that can aid the study of climate perception emergence over time.